Pelayanan Korban Pelecehan Seksual Terhadap Anak Di Provinsi Kepulauan Riau: Fakta Dan Tantangan - Shendy Devendra Armaya; David Tan; Triana Dewi Seroja (Unram Law Review, 2025)
Child sexual abuse is a serious phenomenon that continues to increase in the Riau Islands Province. To address this problem, the government has formed the Regional Technical Implementation Unit for the Protection of Women and Children (UPTD PPA), tasked with providing protection and services to victims. This study aims to evaluate the extent to which UPTD PPA services are effective in handling cases of child sexual abuse, identifying obstacles, and formulating solutions to improve the quality of services.In its implementation, this study used an empirical legal method through a qualitative approach and collected primary data through interviews and observations and secondary data from documents and statistical reports. The research findings revealed that UPTD PPA has attempted to provide legal, psychological, and social services to victims, but its effectiveness is hampered by a lack of trained staff, inadequate facilities, suboptimal cross-sectoral coordination, and low public awareness of the rights of child victims. In addition, social stigmatization and obstacles in providing legal evidence exacerbate victim trauma and hinder the recovery process.This study emphasizes that increasing the capacity of companions, inter-agency coordination, public education, and accelerating the legal process are very important to optimize protection and services for child victims of sexual abuse. It is hoped that the implementation of these recommendations will increase the role of UPTD PPA in creating a safe environment and supporting victim recovery.